Recent trends in parasitic infections of eye- A review - Malhotra, S.; Sharma, S.; K. Bhatia, N.J.; Kumar, P.; Hans, C. (Health, Safety and Environment, 2020)
There are many causes of blindness and those induced by parasitic agents (i.e., Protozoa, Helminths and Diptera) are of major public health concern in developed and developing countries. For example, eye disease caused by river blindness (Onchocerca volvulus), affects more than 17.7 million people inducing visual impairment and blindness elicited by microfilariae that migrate to the eyes after being released by female adult worms in the subcutaneous tissues . Several parasites localize in human eyes as an effect of a specific neurotropism(e.g., Toxoplasma gondii in the foetuses), larval migration(e.g., ascarids, Dirofilaria spp., Trichinella spp.) and, in a few cases, as a primary localization being released directly into the eyes (e.g., Thelazia callipaeda eyeworm and some oestrid fly larvae causing myiasis) Undoubtedly, the parasitic zoonotic diseases and their epidemiology have been changing as result of complex factors including abiotic (e.g., increasing temperatures) and biotic (e.g., demographical changes, political upheaval and land- use practices) that render this topic of great interest for the scientific community Thus the present article focuses on recent trends in all the parasites that are transmitted from animals to humans and affect the human eye.